2007
DOI: 10.1029/2007gl030658
|View full text |Cite
|
Sign up to set email alerts
|

Physical and ecological processes of internal waves on an isolated reef ecosystem in the South China Sea

Abstract: [1] Field measurements at Dongsha Atoll in the northern South China Sea showed frequent drops in daily water temperature up to 8°C during intrusions of large nonlinear internal waves. The internal waves had a period of about 4 hours and velocity amplitude of 0.3 m s À1. Large variations of dissolved oxygen were observed a week after cold-water intrusion, which was followed in another 2 days by a significant increase of chlorophyll content. The 7 -8-day delay suggests that phytoplankton blooms occurred after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 15 publications
4
117
0
Order By: Relevance
“…vertical and horizontal currents, and the turbulent mixing caused by their breaking, they impact a panoply of ocean processes, such as the supply of nutrients for photosynthesis 1 , sediment and pollutant transport 2 and acoustic transmission 3 ; they also pose hazards for manmade structures in the ocean 4 . Generated primarily by the wind and the tides, internal waves can travel thousands of kilometres from their sources before breaking 5 , posing severe challenges for their observation and their inclusion in numerical climate models, which are sensitive to their effects [6][7] .…”
mentioning
confidence: 99%
“…vertical and horizontal currents, and the turbulent mixing caused by their breaking, they impact a panoply of ocean processes, such as the supply of nutrients for photosynthesis 1 , sediment and pollutant transport 2 and acoustic transmission 3 ; they also pose hazards for manmade structures in the ocean 4 . Generated primarily by the wind and the tides, internal waves can travel thousands of kilometres from their sources before breaking 5 , posing severe challenges for their observation and their inclusion in numerical climate models, which are sensitive to their effects [6][7] .…”
mentioning
confidence: 99%
“…slopes facing the open basin remained healthy (Wang et al, 2007). It has been suggested that larvae living in the fluctuating thermal regimes might be physiologically well suited to the more extreme temperature variations (Putnam et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The large internal solitary waves that shoal onto the Chinese continental shelf are highly energetic features that have implications for biological productivity and sediment transport (Wang et al, 2007;Reeder et al, 2011). St.…”
Section: K G Lamb and A Warn-varnas: Shoaling Internal Solitary Wavesmentioning
confidence: 99%